The molecular basis of viral infection - Klasse, P. J. (Per Johan) (Progress in molecular biology and translational science, 2015)
Virology is in a sense both one of the most important precursors and one of the most significant beneficiaries of structural and cellular molecular biology. Numerous breakthroughs in our understanding of the molecular interactions of viruses with host cells are ready for translation into medically important applications such as the prevention and treatment of viral infections. This book collects a wide variety of examples of frontline research into molecular aspects of viral infections from virological, immunological, cell- and molecular-biological, structural, and theoretical perspectives.